2019
DOI: 10.1634/theoncologist.2018-0370
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibitors and Newly Developed Nonalcoholic Fatty Liver Disease in Postmenopausal Patients with Early Breast Cancer: A Propensity Score-Matched Cohort Study

Abstract: Background Unlike tamoxifen, the relationship between aromatase inhibitor use in postmenopausal patients with breast cancer and nonalcoholic fatty liver disease (NAFLD) has not been delineated. Materials and Methods A retrospective analysis of 253 patients with early breast cancer without baseline NAFLD and treated with nonsteroidal aromatase inhibitors was performed. Among them, 220 patients were matched for sex, age, and menstruation status with healthy patients, and the prevalence of NAFLD was compared. NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Totally, 781 relevant studies were extracted from the databases, 41 full-text articles were retrieved for detailed evaluation. Ultimately seven studies with eight cohorts, 3684 patients were enrolled in this meta-analysis [10][11][12][13][15][16][17] . Flowchart of literature selection was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally, 781 relevant studies were extracted from the databases, 41 full-text articles were retrieved for detailed evaluation. Ultimately seven studies with eight cohorts, 3684 patients were enrolled in this meta-analysis [10][11][12][13][15][16][17] . Flowchart of literature selection was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the correlation between NAFLD and breast cancer prognosis remained contentious. Several studies proved patients with NAFLD had worse prognosis 10,11 , while study by Wu et al suggested NAFLD served as a protective factor towards breast cancer progression 12 . Additionally, given that one of the major ET adverse effect was NAFLD, it remained undetermined that whether NAFLD induced by ET had similar prognostic value as common NAFLD.…”
Section: Ivyspringmentioning
confidence: 99%
“…The decrease in substrates of estradiol synthesis pathway, testosterone and DHEA, and the increase in estradiol suggests the possibility of increased aromatase enzyme activity. Clinical studies show that aromatase inhibitors utilized for treatment of breast cancer induce hepatotoxicity [50, 51]. Aromatase overexpression has been reported in hepatitis and hepatocellular carcinoma, but the role of aromatase in liver disorders remains unclear.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recovery of NAFLD was noted 1.2 years following treatment withdrawal [89]. Aromatase inhibitors suppress total estrogen synthesis by more than 90% [93]. In a retrospective analysis of 220 postmenopausal women with early breast cancer without baseline NAFLD, who were matched for age and menopausal status with healthy women, treatment with aromatase inhibitors (anastrozole, 1 mg/day or letrozole, 2.5 mg/day) was associated with increased NAFLD rates (diagnosed with the application of non-invasive fatty liver indices) independently of BMI and underlying T2DM (HR 2.98, 95% CI 1.96-4.53) [93].…”
Section: Evidence In Postmenopausal Womenmentioning
confidence: 99%